Histomorphological Features in the Differentiation of Skin of Spotted Deer (Axis axis), Cattle (Bos indicus) and Goat (Capra hircus) - Nagaraju, G N; Prasad, R V; Jamuna, K V; Ramkrishna, V (Indian Journal of Veterinary Anatomy, 2012)
The histological study was conducted on the skin of spotted deer, goat and cattle. There were three layers in the epidermis of spotted deer, four layers in goat and all the five layers in cattle. The skin thickness was thinnest in spotted deer. The distribution of hair follicles in the horizontal sections of the skin was the most significant and species characteristic feature. Hair follicles in spotted deer were arranged in linear position with only primary follicles. In goat, there was a single row of primary hair follicles associated with 1-2 secondary hair follicles. In cattle, there were only primary follicles scattered in the dermis. Distinct elastic fibres were seen between the follicles in spotted deer only. Sweat glands were present at the junction of the dermis and hypodermis in spotted deer. In case of goat, both sweat and sebaceous glands were located at the base of the hair follicles. Nerve fibres were more distinct in goat as compared to cattle and spotted deer.